Portus, investigaciones geoarqueológicas en el muelle este-oeste - Meléndez, Javier Bermejo; Campos, Juan M. (2023)
Portus, investigaciones geoarqueológicas en el muelle este-oeste collects the scientific results of the geoarchaeological project on the east-west pier of Portus (Rome) developed within the framework of the Archaeological Projects Abroad program of the Ministerio de Cultura y Deporte of the Kingdom of Spain, and also under a collaboration agreement between the University of Huelva and the Parco Archeologico di Ostia Antica. Since 2017, without interruption until the present, various excavation and study campaigns have focused their efforts on the pier via an inter- and multidisciplinary methodology involving archaeologists, geologists, palaeobotanists and palaeontologists. Thus, excavation activities, geophysical prospecting, petrographic, archaeometric studies and architectural analysis have been developed, always with the application of new photogrammetric techniques and laser scanning, which have allowed us to obtain a significant volume of data. Its analysis and interpretation now gives the most extensive and up-to-date picture of one of the most interesting and extensive docks in Portus, with new contributions related to its chronology, with a building phase from the fourth century AD; its construction system, whose foundations have been determined; the surrounding paleoenvironment, with new data related to the silting process of the Claudio inlet; as well as the changes that occured in the transition to the Early Middle Ages, among others.